The Poets of Myanmar - Cummins, Paul (Radical Teacher, 2023)
Since this field is required for the submission to continue, I am including the same biography as in previous screen: Biography Paul Cummins’ Poems have appeared in numerous publications including The New Republic, Poetry LA, Whole Notes, Exquisite Corpse, Coracle, Black Buzzard Review, Rattle, Cooweescoowee, Cloudbank, Rockhurst Review, South Loop Review, Absoloose and Perfume River. Also he has won several poetry prizes and has appeared in many anthologies. In addition, Cummins is an educator, writer and social entrepreneur. From Stanford (B.A.) to Harvard (M.A.T.) to USC (Ph.D.) to classroom teaching 1960-71, he went on to the founding and co-founding of six schools — including private schools such as Crossroads School and TREE Academy, plus Camino Nuevo Public Charter School. From the creation of educational outreach programs such as P.S. Arts and The Coalition for Engaged Education to all his groundbreaking and innovative ventures, Cummins has been a champion for quality education, especially for at-risk, foster and incarcerated youth. His publications include an autobiography, Confessions of a Headmaster, three other books on education, two children’s books, four collections of essays, a biography of a holocaust survivor, Dachau Song, and three volumes of poetry.